SURGICAL TREATMENT OF INTERVERTEBRAL HERNIAS - Isakov B.M.; Mirzayuldashev N.Yu.; Isakov K.B.; Mamadzhanov K.H. (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The paper analyzes the manifestations of lumbar intervertebral hernias in 426 patients undergoing surgical treatment for this reason. The main determining indication for the operation was a pronounced radicular pain syndrome. Some sexual and age-related features of localization and clinical manifestations of lumbar hernias were revealed, as well as a fairly frequent combination of the latter with the phenomena of instability of the corresponding vertebral-motor segment (PDS) - in almost a third of patients with discradicular conflict. The operation of choice for this pathology is the intervertebral microsurgical removal of a herniated disc.